Journal of Indonesian Economy dan Business = Jurnal Ekonomi dan Bisnis Indonesia - Mari Elka Pangestu (Faculty of Economics & Business Universitas Gadjah Mada, 2009)
NO. Penulis ---- Judul Artikel ---- Halaman 1. John Malcolm Dawling ---- Global Recession and Asian Growth : Experience and Prospects ---- 1-21 2. Mari Elka Pangestu ---- Competitiveness Towards ASEAN Economic Community ---- 22-32 3. Ascarya ---- Toward Optimum Synergy of Monetary Policy in Dual Financial / Banking System ---- 33-48 4. Endri ---- Strengthening Financial System Stability Through Enhancing Intermediary Function and Efficiency of Bank Pembangunan Daerah (Regional Development Bank) ---- 49-68 5. Nurul Istifadah ---- The Concentration Pattern and Implication of 2001 Flight Deregulation Policy on Domestic Commercial Flight Industry in Indonesia ---- 69-80 6. Sumiyana ---- Noise as the Impact of Trading Mechanism and Periodic Clearing Procedures : Substantive Evidence From Indonesia Stock Exchange ---- 81-99 7. Euis Soliha & Naila Zulfa ---- The Difference in Consumer Risk Perception between Celebrity Endorser and Expert Endorser in College Advertisements ---- 100-114 8. Diana Zuhroh, Paeawiyati & Eni Lisetyani ---- A Study on the Core Curriculum of Accounting as the Competencies Builder of the Accounting Graduates (A Study on the Accounting Graduates Who Work at Private Companies, State Companies, Non-Profit Organizations, and Public Accountant Firms in Surabaya) ---- 115-134